2017
DOI: 10.1002/ase.1761
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between student engagement with online content and achievement in a blended learning anatomy course

Abstract: Blended learning has become increasingly common in higher education. Recent findings suggest that blended learning achieves better student outcomes than traditional face-to-face teaching in gross anatomy courses. While face-to-face content is perceived as important to learning there is less evidence for the significance of online content in improving student outcomes. Students enrolled in a second-year anatomy course from the physiotherapy (PT), exercise physiology (EP), and exercise science (ES) programs acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
84
2
7

Year Published

2018
2018
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(116 citation statements)
references
References 33 publications
(57 reference statements)
7
84
2
7
Order By: Relevance
“…So for many modern day students who often have minimal time for study, this resource is a fantastic asset -not only do students have a way of finding out what they don't know but they also have a flexible resource that they can access anytime and anywhere to consolidate that knowledge (Collis et al, 1997). These adaptive resources are not only invaluable in anatomy subjects as we have shown here but there is enormous potential for them to be applied to many different disciplines to assist students in assessment preparation particularly when students often have four end of session assessment items due at roughly the same time (Makransky et al, 2016;Green, 2018;Wong et al, 2015). Indeed, this was evident from the student interviews where there was a clear message from students wishing that the resources were available in all subjects.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…So for many modern day students who often have minimal time for study, this resource is a fantastic asset -not only do students have a way of finding out what they don't know but they also have a flexible resource that they can access anytime and anywhere to consolidate that knowledge (Collis et al, 1997). These adaptive resources are not only invaluable in anatomy subjects as we have shown here but there is enormous potential for them to be applied to many different disciplines to assist students in assessment preparation particularly when students often have four end of session assessment items due at roughly the same time (Makransky et al, 2016;Green, 2018;Wong et al, 2015). Indeed, this was evident from the student interviews where there was a clear message from students wishing that the resources were available in all subjects.…”
Section: Discussionmentioning
confidence: 95%
“…Current limitations on how much time students can spend revising anatomy in the laboratory, increased class sizes, staffing constraints and increasing costs of cadaver-based instruction, have led to developments in online technologies. Computer based learning resources have become commonplace in the anatomy curriculum (Green et al, 2018) as evidence suggests that student success is maximised when a combination of pedagogical strategies are employed (Estai & Bunt, 2016). Indeed, there are reports of improvements in student learning and outcomes when traditional methods are replaced with student centered learning and more interactive teaching (Biggs & Tang, 2011;Zwick, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Further analysis revealed that the number of times a student viewed the online videos was the single most important determinant of PT performance. Therefore it does not matter if the lectures are delivered face‐to‐face or online, what matters is that students engage thoroughly with the content (Green et al, ). This also supports the notion that revisiting content is an important factor in student learning (Cook et al, , Bergman et al, ; Zacharis, ).…”
Section: Discussionmentioning
confidence: 99%
“…Data suggest that for students enrolled in online anatomy modules, there is a positive correlation between the number of posts a student contributes to online discussion and their overall final grade (Green et al, 2014(Green et al, , 2018. It is possible that the lack of participation in the live chat and discussion boards may be due to student's irregular use of these platforms to communicate.…”
Section: Improving Virtual Learning Interactions: Reducing the Transamentioning
confidence: 99%